A Corrosion Detection Method for Steel Strands Based on LC Electromagnetic Resonance - Yong Huang; Hang Zhang; Benniu Zhang; Xingxing Li; Xiaoyu Sang; Yi Si; A. Pa Er; Yiwei Zheng; Qiang Yin; Jianhui Jiang (Advances in Materials Science and Engineering)
At present, prestress detection is a worldwide problem. Corrosion has an important impact on the accuracy of the stress detection results of prestressed tendons. Once the steel strands in service is corroded, stress corrosion will occur, which seriously affects the safe operation of the prestressed structure. Based on the LC electromagnetic resonance circuit to detect the prestressing force of steel strands, this research has been successfully applied to the detection of the corrosion rate of steel strands, which lays the foundation for the nondestructive detection of the healthy state of steel strands in the existing structure. In this study, the steel strands were regarded as an external inductor embedded in the LC resonance circuit. After the steel strands was corroded, its electromagnetic characteristics would change, and this change was manifested by the resonance frequency. In this paper, the regular change of the resonance frequency caused by the change of the inductance of the steel wire after corrosion was explained theoretically, and a theoretical model of the relationship between the electromagnetic resonance frequency and the corrosion rate was established. In this study, it was proved through experiments that the LC electromagnetic resonance method can accurately detect the overall corrosion degree of bare steel stranded wires, and a fitting formula for corrosion detection of steel stranded wires was established. Through the analysis and exploration of the test data and test phenomena, it has been found that the action mechanism of the stranded wire decreases with the increase of the corrosion rate and the inductance thereof, which leads to the increase of the resonance frequency. The discovery of these laws will provide an improved basis for the prestress detection of in-service steel strands by LC resonant circuits and make the method to be further applied to practical engineering.